Flame figures in bullous pemphigoid. - Beer, T; Langtry, J; Phillips, W; Wojnarowska, F (1994)
We report a patient with bullous pemphigoid showing prominent flame figures on skin biopsy. Although flame figures are the histological hallmark of eosinophilic cellulitis, they are occasionally seen in a variety of other dermatoses.